The Development of Supervision Process for Instructional Development of Teachers to Promote Self-Directed Learning of Students - Pan-Ngam, Kittisak (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
Instructional supervision is a process of development in teaching behaviors. Instructional supervision improves teachers’ ability to allow students to connect knowledge with learning skills, and have ability to search information and be autonomous. The purposes of this research were to: 1) create the supervision process for instructional development of teachers to promote self-directed learning of students, 2) evaluate the teachers’ knowledge of promoting self-directed learning in students before and after the supervision, and 3) examine their satisfaction of the supervision process. The population for the research was science teachers of grade 5 students in semester 2, academic year 2018, under supervision of Office of Primary Educational Service Area. Thirty of them were selected as sample for this study by multi stage sampling. The research instruments were: 1) the supervision process for instructional development of teachers to promote self-directed learning of students, 2) supervision guide for instructional development of teachers to promote self-directed learning of students, 3) a five-point Likert scale questionnaire, and 4) a test to elicit teachers’ knowledge on promoting self-directing learning. The statistics were employed in data analysis including mean, standard deviation and one sample t-test. Results show that: 1) the supervision process for instructional development of teachers to promote self-directed learning of students includes planning for supervision, acting, reflecting, evaluating and sharing, 2) teaching ability of teachers were at a high level with the mean score of 4.06, 3) the achievement scores after supervision was significantly higher at .001 level; and 4) the teachers have a high level of satisfaction of the supervision process, with the mean score of 4.33. Results of this study can provide supervisors as a tool for supervision in the development of teachers to promote self-directed learning in students. The most important thing is to give feedback to teachers so that the self-assessment results can be used to improve them.